Clinical Governance, Service Quality, and Patient Satisfaction at Community Health Centers: A PLS-SEM Study - Suryadi, Suryadi; Rachmiana , Aida (Journal of Authentic Research, 2026)
Patient satisfaction has become a central benchmark in evaluating primary healthcare quality, yet the organizational mechanisms that drive it particularly clinical governance remain underexplored in the Indonesian context. This study analyzes the direct and indirect influence of clinical governance on patient satisfaction through service quality, and examines its moderating role in strengthening the service quality–patient satisfaction relationship at community health centers (Puskesmas) in Banda Aceh. Unlike previous Indonesian studies that primarily examined service quality as a direct predictor of satisfaction, this study investigates clinical governance as both an antecedent and a moderating mechanism within a unified PLS-SEM framework. A quantitative cross-sectional design was employed with 200 patients recruited from Puskesmas Meuraxa and Puskesmas Ulee Kareng using Disproportionate Stratified Random Sampling (n = 100 per site). Data were collected via structured questionnaires measuring clinical governance, service quality (SERVQUAL dimensions), and patient satisfaction on a five-point Likert scale. Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS was applied to test all hypothesized relationships. Results demonstrate that service quality exerts the most dominant influence on patient satisfaction at both sites (Ulee Kareng: β = 0.861, p < 0.001; Meuraxa: β = 0.700, p < 0.001). Clinical governance significantly influences both patient satisfaction (β = 0.577 and β = 0.318, p < 0.001) and service quality (β = 0.894 and β = 0.811, p < 0.001). Clinical governance also significantly moderates the service quality–patient satisfaction relationship at both facilities. No statistically significant differences were found between the two sites, suggesting successful governance standardization. PLS-SEM findings confirm that strong clinical governance is not merely a structural requirement but a strategic amplifier of service quality that directly and indirectly elevates patient satisfaction in primary care settings. Theoretically, the study positions clinical governance as a higher-order organizational capability that shapes the quality-enabling context of primary care, contributing a governance-centered perspective to patient-satisfaction research in low- and middle-income settings.